The Influence of the Metabolic Syndrome on the Short- and Long-Term Outcome After Carotid Endarterectomy. (April 2017) - Visser, Linda; Vries, Bas M. Wallis de; Mulder, Douwe J.; Uyttenboogaart, Maarten; Veen, Sterre van der; Zeebregts, Clark J.; Pol, Robert A.
The metabolic syndrome (MetS) is a cluster of risk factors for cardiovascular disease. The aim of this study is to determine the influence of MetS on short- and long-term outcome and survival after carotid endarterectomy (CEA). Between January 2005 and December 2014, data from all patients undergoing CEA were prospectively recorded. The metabolic syndrome was defined based on the presence of ≥3 of the following criteria: hypertension, high serum triglycerides, low levels of high-density lipoprotein cholesterol, high fasting serum glucose, and obesity. Primary end points were the occurrence of transient ischemic attack (TIA)/cerebrovascular accident (CVA), myocardial infarction, and mortality. A total of 564 interventions (in 525 patients) were performed, of which 244 (43.3%) were in patients who met the diagnosis of MetS. There were no differences in short- and long-term complications and overall survival between patients with and without MetS. Patients with diabetes mellitus (DM) had significantly more ipsilateral TIA/CVA after 30 days ( P = .001). The presence of MetS has no negative effect on the outcome after CEA. However, patients with DM have a significantly higher risk of ipsilateral TIA/CVA.